2007
DOI: 10.3354/meps334093
|View full text |Cite
|
Sign up to set email alerts
|

Photoacclimation of Stylophora pistillata to light extremes: metabolism and calcification

Abstract: The hermatypic coral Stylophora pistillata has a wide bathymetric distribution (0 to 70 m). Within this range, light intensity decreases exponentially. Deep-water colonies are generally planar in morphology, with the upper part being dark and the bottom-facing part pale. Shallow-water colonies are generally subspherical and ivory in coloration. We studied the effects of photoacclimation on photosynthesis, respiration, and calcification in S. pistillata colonies along its bathymetric range over a reef profile (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
167
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(200 citation statements)
references
References 32 publications
33
167
0
Order By: Relevance
“…Coles & Jokiel 1977), the effect of spatial differences in irradiance are not. However, Mass et al (2007) found that rates of photosynthesis and dark respiration decreased with increasing depth (and decreasing irradiance) over a 70 m depth gradient. A study by Cooper et al (2011) confirmed this pattern but also found that a depth-related shift in Symbiodinium type in the coral Seriatopora hystrix over similar depths correlated with a non-linear response in the photosynthesis: respiration ratio.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Coles & Jokiel 1977), the effect of spatial differences in irradiance are not. However, Mass et al (2007) found that rates of photosynthesis and dark respiration decreased with increasing depth (and decreasing irradiance) over a 70 m depth gradient. A study by Cooper et al (2011) confirmed this pattern but also found that a depth-related shift in Symbiodinium type in the coral Seriatopora hystrix over similar depths correlated with a non-linear response in the photosynthesis: respiration ratio.…”
Section: Discussionmentioning
confidence: 95%
“…While the interaction between Symbiodinium type and patterns of photosynthesis and respiration activity has been investigated over local-scale depth gradients (Mass et al 2007), our understanding of such patterns of variation at larger spatial scales is currently limited. However, a recent study by Hennige et al (2010) of the photosynthesis and respiration activity of corals across an environmental gradient of temperature, light and turbidity confirmed that metabolic rates were governed by acclimatisation to the local environment coupled with adaptation, which was manifested through a shift in Symbiodinium clade for one of their study species.…”
Section: Introductionmentioning
confidence: 99%
“…In low light and nutrient-replete conditions, photoacclimation increases the photosynthetic efficiency in corals (Dustan 1982;Mass et al 2007;Hoogenboom et al 2009) by increasing the areal pigment (e.g., chl a) and light harvesting protein concentrations (Dubinsky et al 1990;Titlyanov et al 2001). The efficiency of the photosystem is proportional to the light absorbed by the photosystem II in the chloroplasts.…”
Section: Introductionmentioning
confidence: 99%
“…the amount of solar radiation incident to the Earth's surface (kW m −2 day −1 ; see equation in the Appendix). Photosynthesis-irradiance (P − I ) curves for corals have been extensively studied, and how their parameters change with local light environment has been well established (Anthony and Hoegh-Guldberg, 2003a;Chalker et al, 1983;Dubinsky et al, 1984;Mass et al, 2007;Porter et al, 1984). These studies show that there is a strong decrease in the saturation intensity as ambient light levels decrease, which corresponds to an increase in the efficiency of photosynthesis.…”
Section: Irradiance (Q Day )mentioning
confidence: 99%
“…Nevertheless, there is evidence that this assumption holds when considering the community average of a coral living in typical reef conditions. For example, Mass et al (2007) reported constant rates of photosynthesis and calcification at 5 and 10 m depths despite a 50 % reduction in ambient light levels, and Hennige et al (2008) demonstrated that Porites lutea from two sites and multiple depths regulates how much light is absorbed in order to maintain a constant load on its photosystem.…”
Section: Irradiance (Q Day )mentioning
confidence: 99%